Recent Advances in Fluorescence Imaging of Traumatic Brain Injury in Animal Models - Lu, Fei; Cao, Jiating; Su, Qinglun; Zhao, Qin; Wang, Huihai; Guan, Weijiang; Zhou, Wenjuan (Frontiers in Molecular Biosciences, 2021)
Traumatic brain injury (TBI) is one of the top three specific neurological disorders, requiring reliable, rapid, and sensitive imaging of brain vessels, tissues, and cells for effective diagnosis and treatment. Although the use of medical imaging such as computed tomography (CT) and magnetic resonance imaging (MRI) for the TBI detection is well established, the exploration of novel TBI imaging techniques is of great interest. In this review, recent advances in fluorescence imaging for the diagnosis and evaluation of TBI are summarized and discussed in three sections: imaging of the cerebral vessels, imaging of brain tissues and cells, and imaging of TBI-related biomarkers. Design strategies for probes and labels used in TBI fluorescence imaging are also described in detail to inspire broader applications. Moreover, the multimodal TBI imaging platforms combining MRI and fluorescence imaging are also briefly introduced. It is hoped that this review will promote more studies on TBI fluorescence imaging, and enable its use for clinical diagnosis as early as possible, helping TBI patients get better treatment and rehabilitation.